2012
DOI: 10.1007/s10661-012-2796-5
|View full text |Cite
|
Sign up to set email alerts
|

No relationship found between mercury and lead concentrations in muscle and scales of chub Squalius cephalus L.

Abstract: We examined the relationship between muscle and scale mercury (Hg) and lead (Pb) concentrations in chub Squalius cephalus L. from six riverine sites in the Czech Republic in order to determine whether scale analysis alone could provide a nonlethal and convenient method for prediction of heavy metal concentration in muscle tissue. Our results confirm tissue-specific heavy metal accumulation in chub, with Hg tending to accumulate primarily in muscle tissue and Pb in scales. We found no significant relationship, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Conversely, Valová et al, (2013) found no significant correlation between Hg concentrations in scales and muscle of chub (Squalius cephalus), proposing that scales cannot be used as a reliable tool for metal analysis until further research has been done on methodology, particularly regarding the cleaning treatment of scales. Farrell et al (2000) also found no relationship between Hg (as well as Se) concentrations in scales and muscle of Arctic grayling (Thymallus arcticus).…”
Section: Mercury In Scales/fins Compared To Musclementioning
confidence: 96%
See 2 more Smart Citations
“…Conversely, Valová et al, (2013) found no significant correlation between Hg concentrations in scales and muscle of chub (Squalius cephalus), proposing that scales cannot be used as a reliable tool for metal analysis until further research has been done on methodology, particularly regarding the cleaning treatment of scales. Farrell et al (2000) also found no relationship between Hg (as well as Se) concentrations in scales and muscle of Arctic grayling (Thymallus arcticus).…”
Section: Mercury In Scales/fins Compared To Musclementioning
confidence: 96%
“…Nonlethal sampling has advantages over the whole tissue sampling procedures À it provides a possibility to collect larger samples, as well as to sample rare and endangered species without causing mortality (Baker et al, 2004). Most studies on nonlethal sampling have focused on monitoring of mercury (Gremillion et al, 2005;Schmitt and Brumbaugh, 2007;Rolfhus and Sandheinrich, 2008;Červenka et al, 2011;Valová et al, 2013;Cerveny et al, 2016). Commonly considered nonlethal sampling techniques in fish include the analysis of scales and fins, as well as tissue biopsy of blood, liver, or muscle via needles or punches (Valová et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Lake et al (2006) also reported considerable variation in the muscle-scale Hg relationship, and therefore suggested that scales be used only as a first level screening tool to assess general trends in muscle tissue Hg concentrations. Other investigators did not detect significant relationships between total Hg concentrations in fish muscle tissue and (unwashed) scales for individual freshwater species, including chub Squalis cephalus , bream Abramis brama , perch Perca fluviatilis , and roach Rutilus rutilus (Červenka et al 2011; Valová et al 2013) (Table 3). In the present study, the relatively high level of uncertainty within the regression models indicates that scales were an ineffective tool for estimating muscle tissue Hg concentrations in marine fishes.…”
Section: Resultsmentioning
confidence: 97%